MacDonald, Brenda. Brenda MacDonald interview, August 19, 2013. - McDougall, Claire (2013)
"Brenda MacDonald discusses her childhood, particularly the games and play activities that occupied her peer group and all the children in her neighbourhood. She also talks about the close-knit nature of the community in which she grew up, about visiting with family, about Sunday traditions and foodways. Introduction: BM gives some biographical information, DOB, and first memories / BM starts listing and briefly describing games she played as a child: Hoist Yer Sails and Run/Hide n’ Seek/Simon Says/Red rover/London Bridge/Marbles/Skipping (French and German)/Spotlight/Jacks/Button Button/Handball/Softball/Swimming/Hockey/Skating/ Roller-skating/ Sliding/ BM talks about a local man who would build a large igloo every winter, with seats inside it, where local youth (mainly older teenagers) would gather to tell stories./ Make Believe/Mimicry: House/ School/Grocery Store/Cowboys and Indians/BM’s husband Bob comes in at this point and she introduces him. /Bike Riding/Blueberry Picking/Hopscotch/Ball Game: Eeny Clapsy Whirl around the Bapsy/ Eeny Meeny Miney Moe – counting out rhyme/ Cat’s Cradle/Knitting/Boggers/Nicky Nicky Nine Doors/Phone rings and the recording is paused./Hula Hoops/Stilts/Card games (Crib, Crazy Eights, Old Maid, Fish)/BM talks about going to movies at the Paramount and???. She also discusses spending evenings and weekends at the local rec centre with her peers, playing volleyball, basketball, card games and board games, and going to the Plaza Bowl on Sundays for dances./BM talks about the neighbourhood of her childhood./BM gives a more detailed description of the rules of Hoist Yer Sails and Run/discusses the kind of games she played in the school yard and roller-skating in the school gym on weekends./BM talks about trading comics and give more details about the rules of Hide n’ Seek and Spotlight./Talks about playing with Barbies, and about the clothing her mother made for her Barbie. Talks about styling the hair of dolls she had and playing beauty parlour./BM talks about running lemonade ...